Impact of Risk Supply Chain Management and International Debt Market Indicators on GDP - Valery L Abramov; Igor Alexeevich Balyuk; Aleksandr Sergeevich Fedyunin (International Journal of Supply Chain Management, 2019)
Financial and economic globalization has significantly increased the total amount of external debt of the different countries of the world. An aggravation of the problem of globalization of the external debt prevents the restoration of stability and achieving sustainable growth in the current global economy. In this regard, at present various countries and groups of countries strengthen management of external borrowings at the national and regional levels. The author has made an attempt to evaluate an impact of the major international debt market indicators and risk supply chain management on GDP. The paper is focusing on an econometric analysis of the hypothetical linkage between the major international debt market indicators and risk supply chain management on GDP growth. A correlation and regression analysis was applied as the basic method of econometric study. The paper has a conclusion that in the world the most effective external debt instruments stimulating the growth of GDP are international syndicated loans and gross issues of international debt securities.